A Comparative Study of Reason in Islamic Education with Emphasis on Imami and Sunni Jurisprudence - Fatemh Karimi; Mohammad Jafari Harandi (Comparative Education Society of Iran ( CESIR), 2021)
Although Iran is a religiously pluralistic society, but given the sovereignty of the political system of the Islamic Republic, it seems there is a need to know principles of Islamic education. One of the important issues that has a long history among the philosophers of the Islamic world is the concept and role of reason in jurisprudential sources and its impact on education of young generation. The purpose of this research was to explain the role and position of reason in Islamic education with emphasis on comparing Imami and Sunni jurisprudence. In terms of method, the present study is a hermeneutical research using author-centered type. Researchers have used the documentary and sequential analysis methods for collection and analysis of data respectively. Findings show that Imami and Sunni jurisprudence are similar in accepting reason as one of the most important means for understanding religious subjects, while there is disagreement between these two schools of thought about the scope and position of reason. Also, the findings of research indicated that in Sunni jurisprudence, there were jurists who believed in the role of reason, although Imami jurists mainly reject both extremist and extremist rationalism. In addition, the research findings showed that while Imami jurisprudence places special emphasis on the role of reason, the prevailing atmosphere in the Iran's educational system and the current interpretation of Islamic education is mainly based on the following principles such as ignoring individual differences of learners, emphasizing imitation, denial of questioning and lack of a creative and rational role in the process of teaching and learning. Given these findings, the need for educational policymakers to coordinate the process of Islamic education with Imami jurisprudence - with a focus on the role of reason - seems necessary.